Austreibvorrichtung zum Herauslösen des Kegelschafts eines Werkzeugs aus einer Werkzeugaufnahme - LAI, CHIN-YI (2003)
A Mohs tapered handle remover enables a user to remove a bit by rotating a knob on a first end of the device to actuate the device. The knob, through a threaded interface, drives a slide rod outward. The slide rod causes a raising block to separate from a slide seat, thereby driving the bit out of the handle. The device enables the user to use rotational force instead of a direct force to remove the bit.